2004
DOI: 10.2460/ajvr.2004.65.964
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic relevance of qualitative proteinuria evaluated by use of sodium dodecyl sulfate-agarose gel electrophoresis and comparison with renal histologic findings in dogs

Abstract: SDS-AGE of urinary proteins in dogs represents a noninvasive test with high sensitivity for identifying glomerular and tubulointerstitial damage, but low specificity limits its validity as a stand-alone test to differentiate between glomerular and tubulointerstitial lesions. The test is particularly useful for identifying dogs with advanced tubulointerstitial disease but cannot be used to characterize glomerular disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 32 publications
3
61
0
1
Order By: Relevance
“…The electrophoresis patterns of the healthy dogs in this study appeared representative of normal urine samples, and similar results have been obtained by other authors . In the current study, where in total 3 different bands were observed in urine of healthy dogs, albumin was the most predominant, albeit faintly stained band.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The electrophoresis patterns of the healthy dogs in this study appeared representative of normal urine samples, and similar results have been obtained by other authors . In the current study, where in total 3 different bands were observed in urine of healthy dogs, albumin was the most predominant, albeit faintly stained band.…”
Section: Discussionsupporting
confidence: 91%
“…Under physiological circumstances, the renal processes of glomerular filtration, tubular reabsorption, and tubular secretion regulate the quantity of protein in urine of dogs . The qualitative protein excretion in dogs is characterized by specific proteinuric patterns that can reflect renal injury at various sites of the nephron . For instance, glomerular proteinuria occurs when the selective permeability of the glomerular filtration barrier is altered and thereby leads to filtration of molecules whose size or combined size and charge would normally prevent this.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to serum renal markers and GFR, urinary markers are gaining interest in veterinary medicine, because of their potential for early detection of renal dysfunction and ability to localize the insult to a particular part of the nephron [19], [20], [21]. These markers include high molecular weight (HMW) proteins such as immunoglobulin G (IgG), intermediate (I)MW proteins such as albumin (ALB), low (L)MW proteins such as retinol-binding protein (RBP) and urinary enzymes such as N-acetyl-β-D-glucosaminidase (NAG) [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…No data regarding urine analysis in cetaceans have been found for comparison, but considering domestic animals, cut-off values between proteinuric versus non proteinuric animals are <0.5 in dogs and <0.4 in cats, and an UPC value >2.0 is strongly suggestive of glomerular disease [9]. SDS-AGE confirmed the glomerular origin of proteinuria, since these proteins have a greater molecular weight than albumin [19]. Surprisingly, in SDS-AGE analysis, no band at the expected molecular weight of myoglobin (18 kDa), was evident, despite myoglobin’s evidences in the Bowman’s space and in the tubular lumens observed with IHC examination.…”
mentioning
confidence: 99%